The The Effect Of Transformational Leadership And Work Environment On Job Satisfaction Through Motivation As A Mediating Variable Among Generation Z Employees In Kendal Regency - Rinandi Nadila Ade Kurnia; Gregorius N. Masdjojo (UNIVED Press, 2026)
This study aims to analyze the influence of transformational leadership and work environment on job satisfaction among Generation Z employees in Kendal Regency, with work motivation as a mediating variable. A quantitative approach was employed using Partial Least Square (PLS) analysis with SmartPLS 4.0. The study involved 160 respondents who are Generation Z employees in Kendal Regency. The results indicate that both transformational leadership and work environment have a positive and significant effect on job satisfaction. Furthermore, work motivation is found to mediate the relationship between transformational leadership and job satisfaction, as well as between work environment and job satisfaction. These findings highlight the important role of work motivation as a mediating mechanism in enhancing employee job satisfaction. Overall, this study suggests that improving leadership quality and creating a supportive work environment can enhance employee motivation, which in turn increases job satisfaction among Generation Z employees.